The Great War and modern memory - Fussell, Paul, 1924-2012. (New York : Oxford University Press, 2000)
Landmark study of World War I, describing its effects on the nation.
Originally published: New York : Oxford University Press, 1975.
Contains a new afterword.
Includes bibliographical references and index.
Keywords: English literature -- 20th century -- History and criticism; World War, 1914-1918 -- Great Britain -- Literature and the war; Memory in literature; War and literature; World War, 1914-1918 -- Poetry; World War, 1914-1918, in literature; World War, 1914-1918 -- Literature and the war; World War, 1914-1918 -- Campaigns -- Western Front